If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x/3)+7=5
We move all terms to the left:
-(x/3)+7-(5)=0
We add all the numbers together, and all the variables
-(+x/3)+7-5=0
We add all the numbers together, and all the variables
-(+x/3)+2=0
We get rid of parentheses
-x/3+2=0
We multiply all the terms by the denominator
-x+2*3=0
We add all the numbers together, and all the variables
-1x+6=0
We move all terms containing x to the left, all other terms to the right
-x=-6
x=-6/-1
x=+6
| (x-2)^3-x(3+x)(x-3)+6x^2=0 | | 11h=-121 | | -5/6x-7/9x=-102 | | 3.4x+25=11.56+5x | | 5x−2/11=−7 | | Y=-x²+40 | | 13=k-4 | | m-2=20 | | 5x−211=−7 | | 447+h=951 | | 4=3n–2 | | 4(2-6m)=6(-4m) | | 16x–3(4x+5)–2x=5 | | 2x²-35x=0 | | 18x+6=2x+14 | | 10x+4×6=360 | | -20x+5x=1000 | | 13(12x−24)=16 | | 10a+8-2a=48 | | 5-2(4a-2)=25 | | 2.05(3x-4)-0.5x=2.75 | | 4/x=-2/7 | | -11.6x-4.9x=154 | | 4x-5+8x=4(3x+1) | | 6x+4+5x+10=180 | | |x+7|+9=3 | | 9x-5/5x-5=2/1 | | 7y+5y=48 | | 4(-2x+7)=28-8x | | 30+6x=6 | | 4.2v=63.0 | | -6x-8=-3x+7 |